2019
DOI: 10.1080/14786419.2019.1616729
|View full text |Cite
|
Sign up to set email alerts
|

A new uridine derivative and a new indole derivative from the coral-associated actinomycete Pseudonocardia sp. SCSIO 11457

Abstract: A new uridine derivative 11457A (1), and a new indole derivative 11457B (2), together with a known compound 1H-indole-2-carbaldehyde (3), were characterized from the fermentation broth of the actinomycete Pseudonocardia sp. SCSIO 11457, an isolate associated with the scleractinian coral Galaxea fascicularis. Upon detailed spectroscopic analysis, 11457A (1) was identified as uridine analog, and 11457B (2) was elucidated as an indole derivative 2-hydroxy-1-(1H-indol-2-yl)pentane-1,4-dione.Biological evaluation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…In addition, compounds 60 and 64 showed moderate activity against four cell lines (A549, BGC823, HCT116, HepG2) with the IC 50 values ranging from 5.33 µM to 19.7 µM, and also exhibited the most potent antitumor activity against U87MG cell line with IC 50 values of 0.50 µM and 2.42 µM, respectively. On comparing the structure and activity of analogs (60)(61)(62)(63)(64), it was found that the modification of the tetronolide skeleton affected the in vitro antitumor activity to some extent. Tetrocarcin F1 (S24) was inactive, indicating that the sugar moiety at C-9 position could play an important role in the antitumor activity.…”
Section: Alkaloidsmentioning
confidence: 99%
“…In addition, compounds 60 and 64 showed moderate activity against four cell lines (A549, BGC823, HCT116, HepG2) with the IC 50 values ranging from 5.33 µM to 19.7 µM, and also exhibited the most potent antitumor activity against U87MG cell line with IC 50 values of 0.50 µM and 2.42 µM, respectively. On comparing the structure and activity of analogs (60)(61)(62)(63)(64), it was found that the modification of the tetronolide skeleton affected the in vitro antitumor activity to some extent. Tetrocarcin F1 (S24) was inactive, indicating that the sugar moiety at C-9 position could play an important role in the antitumor activity.…”
Section: Alkaloidsmentioning
confidence: 99%
“…Finally, uradine is interesting, as this metabolite may well be important to the coral holobiont but appears to be associated more with the corals' microbiome rather than the host itself. Fang et al (2019) showed that uradine has high antibacterial capabilities against pathogenic bacteria and is derived from a coral associated actinomycete (Fang et al, 2019). Increased amounts of uridine in thermally stressed corals could indicate a response of the coral holobiont to rising temperatures, acting as a line of defense in preparation for disease infection and is therefore worthy of further investigation in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…SCSIO 11457, a CAB from the stony coral Galaxea fascicularis (Fang et al . 2019). All three compounds, termed nucleoside antibiotics, show low antibacterial activity against the human pathogens S. aureus , MRSA, and Acinetobacter baumannii , and the coral pathogen V. alginolyticus (Fang et al .…”
Section: Secondary Metabolites From Cabmentioning
confidence: 99%
“…All three compounds, termed nucleoside antibiotics, show low antibacterial activity against the human pathogens S. aureus , MRSA, and Acinetobacter baumannii , and the coral pathogen V. alginolyticus (Fang et al . 2019). The antibacterial activity of the three compounds increased in the presence of bacterial symbionts of G. fascicularis , showing how combined effects of bacteria can increase the resistance of corals to pathogens in a system (Fang et al .…”
Section: Secondary Metabolites From Cabmentioning
confidence: 99%
See 1 more Smart Citation